The intergenerational transmission of risk and trust attitudes - Thomas Dohmen; Armin Falk; David Huffman (Center for Economic Studies and ifo Institute (CESifo), 2008)
Recent theoretical contributions depart from the usual practice of treating individual attitude endowments as a black box, by assuming that these are shaped by the attitudes of parents and other role models. Attitudes include fundamental preferences such as risk preference, and crucial beliefs about the world, such as trust. This paper provides evidence on the three main mechanisms for attitude transmission highlighted in the theoretical literature: (1) transmission of attitudes from parents to children; (2) positive assortative mating of parents, which tends to reinforce the impact of parents on the child; (3) an impact of prevailing attitudes in the local environment. Investigating these mechanisms is important because they are crucial assumptions underlying a large literature. It also sheds light on the basic question of where individual attitude endowments come from, and the factors that determine these drivers of economic behavior. The findings are supportive of attitude transmission models, and indicate that all three mechanisms play a role in shaping economically relevant attitudes.
Keywords: D1; D8; J12; J13; J62; Z13; 330; risk preferences; trust; intergenerational transmission; cultural economics; family economics; assortative mating; social interactions; SOEP; Meinung; Risikoaversion; Vertrauen; Familiensoziologie; Generationenbeziehungen; Eltern; Kinder; Deutschland